Self-focusing of radiation in non-uniform mediums - Buts, A.V.; Buts, V.A.; Churyumov, G.I. (Вопросы атомной науки и техники, 2005)
The possibility of self-focusing in propagating the rays in the non-uniform mediums is shown. This self-focusing is similar to a Veksler-Mac-Millan’s autophasing in the theory of accelerators. The self-focusing of the rays are able to weaken essentially an effect of random non-uniformities and to increase the threshold of development of stochastic instability. Показана можливість автофазування променів, що поширюються в неоднорідних середовищах. Це автофазування аналогічне автофазуванню Векслера-Мак-Міллана в теорії прискорювачів. Автофазування променів істотно послабляє вплив випадкових неоднорідностей і збільшує поріг розвитку стохастичної нестійкості. Показана возможность автофазировки лучей, распространяющихся в неоднородных средах. Эта автофазировка аналогична автофазировке Векслера-Мак-Миллана в теории ускорителей. Автофазировка лучей существенно ослабляет влияние случайных неоднородностей и увеличивает порог развития стохастической неустойчивости.